Validation of the Perceived hope scale in Arabic-speaking adults living in Gaza in the midst of war, destruction and death - Feten Fekih-Romdhane; Kamel Jebreen; Tasnim Swaitti; Mohammed Jebreen; Eqbal Radwan; Wafa Kammoun-Rebai; Mahmoud A. Abu Samra; Souheil Hallit (Archives of Public Health)
Abstract Background Despite its obvious relevance for clinical practice and research, it is surprising that presently no hope measure is available for use among Arabic-speaking populations, especially the most vulnerable ones who have been going through major humanitarian crises. This paper aimed to provide novel insights into psychometric information on the psychometric properties of an Arabic translation of the Perceived Hope Scale (PHS) in Palestinians living in Gaza who have endured several months of suffering since the war began in October 2023. Method This study had a cross-sectional design and applied a quantitative research approach. It was carried-out over a one-month period (September 2024) using an anonymous self-report questionnaire that was shared through social networks and the snowball sampling technique. A total of 534 Arabic-speaking Palestinian adults aged over 18 years and currently living in Gaza took part in the study. We conducted a confirmatory factor analysis (CFA) via the SPSS AMOS v.29 software, using the maximum likelihood method to obtain parameters estimates. Results The fit indices of the one-factor solution reached the standards of good model fit, with excellent internal consistency (Cronbach’s alpha = 0.90). Invariance was established in our sample at the configural, metric and scalar levels in terms of gender groups. PHS scores significantly and positively correlated with religiosity, resilience and post-traumatic growth. In addition, PHS inversely correlated with anxiety and depression. Conclusion Overall, our results add to the measurement assessment of the PHS, lending further support to its value as a sound measure to assess perceived hope in a new context and cultural background of Arabic-speaking adults and fragile survivors of several decades of war that dramatically escalated over the past months.